Analysis Of Factors Causing Students To Learn Slowly At UPTD SD Negeri 124398 Pematangsiantar: Case Study - Saragi, Yesiska; Purba, Natalina; Purba, Jon Roi Tua (Lembaga Riset dan Inovasi Almatani, 2026)
This study aims to analyze the factors causing slow learning in students with RS at the UPTD SD Negeri 124398 Pematangsiantar. This study used a qualitative approach with a case study method. Data were obtained through interviews, observation, and documentation, then analyzed descriptively with reference to relevant theories and research. The results showed that RS students experienced obstacles in the learning process, characterized by low academic abilities, especially in reading, understanding instructions, and completing learning assignments. Students also took longer to understand the material than their classmates. In addition, it was found that students had low concentration and learning motivation, were easily distracted, were less active in learning, and lacked confidence in participating in classroom learning activities. The factors causing slow learning in RS students were influenced by internal and external factors. Internal factors include low academic ability, lack of concentration, low learning motivation, and underdeveloped self-confidence. Meanwhile, external factors include lack of learning support at home, limited parental attention, an unsupportive learning environment, and the students' health conditions from an early age. The study concluded that slow learning is the result of an interaction between internal and external factors that influence each other. Therefore, collaboration between teachers, parents, and schools is necessary to provide appropriate support so that students' learning abilities can develop optimally.